Outcomes With Retrograde Versus Antegrade Approach in Chronic Total Occlusion Revascularization - Mohamed Hussien Abd Elmaksoud ; Mohamed Ibrahem Mustafa; Abd Al-Salam El-Sayed Hussein; Mohey Eldeen Abo Al-Fetouh Salem (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The retrograde approach is considered a paradigm shift development in CTO PCI and has become an integral part of the contemporary CTO PCI armamentarium. It increases the success rates but also carries a risk of complications and should, therefore, be used cautiously by experienced operators and centers. The aim of the current study was to compare efficacy and safety of the antegrade and retrograde approaches to determine the best type of approach for CTO-PCI. The study included 60 patients as a comprehensive sample, diagnosed with chronic total occlusion proven by at least with one radiological method either CT coronary angiography scan or Coronary angiography. Complete history taking, physical Examination, 12 lead ECG and conventional transthoracic echocardiography were performed to all patients. Patients were then divided into two groups one with antegrade approach and the other group with retrograde approach, both groups were followed up to detect Primary endpoints during hospital admission were in-hospital mortality, myocardial infarction (MI), need for urgent revascularization, need for urgent pericardiocentesis, contrast-induced nephropathy, procedural success, procedural time, fluoroscopy time, and contrast volume. Secondary endpoints which start after hospital discharge and last for 6 months included long-term outcomes: all-cause mortality, MI, target lesion revascularization (TLR), and target vessel revascularization (TVR). There was no statistically significant difference between both groups regarding ECG findings. Concerning the 2D Transthoracic Echo measures of the studied groups, there was no statistically significant difference between both groups regarding 2D transthoracic Echo measures including EF and WMSI. The predominant occluded vessel of antegrade approach group was LAD artery (50%), meanwhile, that of retrograde approach group was RCA (63.3%). There was a statistically significant difference in the type of CTO vessel between both groups. The success rate was significantly higher in patients subjected to retrograde approach than those subjected to antegrade approach (90% vs. 66.7%, p=0.028). However, the retrograde approach took significantly longer procedure time, fluoroscopy time and more contrast volume  than the antegrade approach. Regarding the primary outcome during hospital stay, there was no statistically significant difference between both groups regarding the incidence of mortality, MI, CIN, need for urgent revascularization and pericardiocentesis. During follow up of the patients for 6 months after discharge, no statistically significant difference was detected between both groups as regard the secondary endpoints. The incidence of all-cause mortality was 13.3% for the antegrade approach group and 10% for the retrograde approach, incidence of MI was 13.3% for antegrade approach and 10% for retrograde approach. Furthermore, the incidence of TLR was 23.3 for the antegrade approach and 16.7% for the retro grade approach and finally the incidence of TVR was 10% for the antegrade approach and 13.3% for the retrograde approach. So we can safely conclude that the retrograde approach can be frequently used as the primary CTO-PCI strategy, especially for more complex CTO lesions and reattempts procedures. However careful follow up is highly recommended during and after the retrograde approach for PCI to CTO vessels